Eating disorders and anxiety among high school students in Western area of Turkey - Unal, Egemen; Aydin, Resat; Gokler, Mehmet Enes; Unsal, Alaettin (International Journal of Research in Medical Sciences, 2017)
Background Eating disorders (ED) are the one of the most common chronic illness among adolescents. The aim of the present study was to investigate eating disorders and it's associations between anxiety among high school students in Sivrihisar in Eskisehir, Turkey. Methods: This cross-sectional study was carried out in the high school students of center of Sivrihisar between 01 January 2014 and 28 February 2014. The questionnaire prepared according to literature, consisting of 3 parts (socio-demographic characteristics, eating attitude test (EAT-40) and beck anxiety inventory (BAI)). The students completed questionnaire in the presence of a member of the research team. The data collected were self-reported by the students. Results: Of the study group 64.4% (n=625) were females and 35.6% (n=345) were males. The prevalence of eating disorder was 13.0% (n=126). The mean and standard deviation of students' total score of EAT-40 were 18.80±9.88 (ranged 3 to 95). The mean and standard deviation of students' total score of BAI were 20.32±12.32 (ranged 0 to 63). The positive weak correlation was found between the total scores of EAT-40 and BAI (r=0.178; p=0.001). Conclusions: ED is an important health problem for adolescents. On the studies upon epidemiology of ED towards high school students, socio-economic factors should be assessed in more detailed and more comprehensive perspective.